“Etnobotánica e identificación cualitativa de principios activos en plantas medicinales del Refugio De Vida Silvestre Laquipampa, Incahuasi, Ferreñafe, Lambayeque - 2018.” - RIOS GUTIERREZ, Danna Anny (2019)
Since ancient times, the human being has been used medicinal plants to treat various diseases, these produce phytoconstituents that exert beneficial action in the living organism. However, their studies are important to support the therapeutic effectiveness, therefore, the aim of the study was to know the qualitative characteristics of the ethnobotanical study and qualitatively identify the active principles in medicinal plants of Laquipampa Wildlife Refuge (LWR). It was done in two phases: The field phase was carried out in the buffer zone and in the Natural Protected Area LWR and the laboratory phase, in the Enzyme Technology and Natural Products laboratory, Faculty of Biological Sciences. 23 interviews were made, determining 90 plants for medicinal use, being the most used: “cholo gordo” “matico”, “luchaj”, “santa maría”, “moradilla”, “zapatito”, “culantrillo”, “verbena”, “cola de caballo” and “palo santo”. The medicinal category with the largest number of species: gastrointestinal problems (39%) and other disorders (52.3%), the most used part were the leaves (61.2%), preparation as Infusion (60%) and the field collection (97.8) %). From the qualitative analysis, it was found that the species studied contain cardenolides, steroids, tannins, flavonoids (90%), saponins (80%) and alkaloids (50%) respectively. It was determined that 100% of the analyzed species contain active ingredients that justify their possible therapeutic use.